Upregulation of ERK1/2-eNOS via AT2 Receptors Decreases the Contractile Response to Angiotensin II in Resistance Mesenteric Arteries from Obese Rats - Hagihara, Graziela N. (Public Library of Science, 2014)
It has been clearly established that mitogen-activated protein kinases (MAPKS) are important mediators of angiotensin II (Ang II) signaling via AT1 receptors in the vasculature. However, evidence for a role of these kinases in changes of Ang II-induced vasoconstriction in obesity is still lacking. Here we sought to determine whether vascular MAPKs are differentially activated by Ang II in obese animals. The role of AT2 receptors was also evaluated. Male monosodium glutamate-induced obese (obese) and non-obese Wistar rats (control) were used. The circulating concentrations of Ang I and Ang II, determined by HPLC, were increased in obese rats. Ang II-induced isometric contraction was decreased in endothelium-intact resistance mesenteric arteries from obese compared with control rats and exhibited a retarded AT1 receptor antagonist response. Blocking of AT2 receptors and inhibition of either endothelial nitric oxide synthase (eNOS) or extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) restored Ang II-induced contraction in obese rats. Western blot analysis revealed increased protein expression of AT2 receptors in arteries from obese rats. Basal and Ang II-induced ERK1/2 phosphorylation was also increased in obese rats. Blockade of either AT1 or AT2 receptors corrected the increased ERK1/2 phosphorylation in arteries from obese rats to levels observed in control preparations. Phosphorylation of eNOS was increased in obese rats. Incubation with the ERK1/2 inhibitor before Ang II stimulation did not affect eNOS phosphorylation in control rats; however, it corrected the increased phosphorylation of eNOS in obese rats. These results clearly demonstrate that enhanced AT2 receptor and ERK1/2-induced, NO-mediated vasodilation reduces Ang II-induced contraction in an endothelium-dependent manner in obese rats.